Exploration of Digitalization Transition in Financial Reporting: Case Study of MSMEs Ayam Geprek Akbar Pare - Wildhi, Nisak Zahrotul; Widodo, Moch. Wahyu; Fauji, Diah Ayu Septi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research objectives: The purpose of this study is to explore the transition of conventional to digital financial reporting systems in Ayam Geprek Akbar Pare MSMEs. Method: This research uses a qualitative method with descriptive. Data collection techniques were carried out through direct observation and in-depth interviews of financial reporting activities in the field. Research Findings: This study's findings reveal that Digitalization as an Improvement in Effectiveness and Efficiency of Financial Reporting,  as a Tool to Minimize Errors, as a Tool to Facilitate Financial Report Monitoring Theoretical contribution/Originality: This research makes an important contribution in identifying the perceived benefits in this digitization process. Implications of Practice / Policy: The results of this study can serve as a guide for other businesses facing similar challenges, as well as provide input for financial technology developers to create solutions that suit the needs of MSMEs. Research limitations: This research is limited to the financial reporting of Ayam Geprek Akbar Pare MSMEs.